Attribution of Romanian AUR Party Chairman George Simion's Political Communication to Gain Community Support (Case Study of Romania's Membership in the EU) - Prihartadi, Bambang; Widaningsih, T. Titi; Budianto, Heri; Bakti, Andi Faisal; Rosadi, Udi (International Journal Labs, 2025)
The emergence of the AUR Party on September 19, 2019, led by George Simion, is a socio-political picture of Romania. AUR was established ahead of the 2020 local and parliamentary elections. In the local elections, AUR received 1 percent of the vote and in the parliamentary elections received 9 percent of the vote. AUR campaigns on four programs: family, nation, orthodox Christians, and freedom. In the 2024 parliamentary elections, AUR received 18 percent, the second largest after the PSD Party with 22.8 percent. The purpose of this research is to uncover the meaning, explore understanding, and analyze George Simion's efforts to gain the support of the Romanian people within the framework of Ramania's membership in the EU by using the integration of Heider's attribution theory with Dan Nimmo's political communication theory. The results of the study explain that there was an increase in votes in the Parliament. George Simion's campaign received increased public support in the parliamentary and presidential elections. On the other hand, there was resistance from the community which was manifested in the second round of the presidential election which was won by Nicorsur Dan, from the independent pro-EU group. George Simion 's defeat in the presidential election was analyzed through George Simion 's political communication attribution theory.